Analisis Deskriptif Kepemimpinan Managerial Grid di Lingkungan Perguruan Tinggi - Albert Kurniawan (Jurnal Manajemen Maranatha, 2016)
The aim of the research is to describe and analyze the appropriate leadership style students in accordance with managerial grid view. Dimension managerial grid are concerned for Relationship Orientation and Task Orientation.This study using explanatory method with quantitative approach. The data were obtained using questionnaire and observation. This research is using non probability method which is Puposive Sampling and it took 67 students. The resultshave shown Leadership Grid 67 students. The results of the research reveal that students implements leadership style of managerial grid of (8,2) (7,9). This is indicated by mean score of subordinate orientation, i.e. 8,2 and mean score of taskorientation, i.e. 7,9.Keywords: Leadership Style, Managerial Grid, Relationship Orientation, Task Orientation